Challenges in Vibrio parahaemolyticus infections caused by the pandemic clone. (11th March 2019) - Han, Dongsheng; Yu, Fei; Chen, Xiao; Zhang, Rui; Li, Jinming
Vibrio Parahaemolyticus infections caused by the pandemic clone have become a global public health issue. The pandemic clone includes over ten sequence types and 49 serotypes. Several markers such as toxRS /new, orf8 and genomic islands were considered specific for pandemic strains, but subsequent studies later confirmed a lack of specificity. Thus, identifying stable indicators for the pandemic clone is still an open question. In recent years, several environmental pandemic strains are growing, constituting a new threat to seafood safety and human health. Traditional methods show limited discrimination in studying the microevolution of pandemic strains. For example, multilocus sequence typing divides many pandemic strains into ST3 type, making it difficult to further distinguish the variability within ST3 strains from different contexts. When using a whole genome sequencing-based technique, strains including those with the same sequence type, could be well separated. Whole genome sequencing-based technology also played important roles in dissecting the evolution process and revealing the mechanism underlying rapid serotype conversion within pandemic strains. In addition, the emergence of multiple-antibiotic resistant pandemic strains needs attention. Altogether, we are facing many challenges posed by pandemic V. parahaemolyticus strains, which need to be resolved in future studies.